Interplane bulk motion analysis and removal based on normalized cross‐correlation in optical coherence tomography angiography. Issue 7 (13th May 2020) - Fan, Jinyu; He, Yi; Wang, Pinghe; Liu, Guangxing; Shi, Guohua
Abstract: Bulk motion seriously degrades the image quality of optical coherence tomography angiography (OCTA). Conventional correction methods focus on in‐plane displacement, while the bulk motion component perpendicular to B‐scans also introduces noise. This work first presents an evaluation of this component using a specific scan protocol and an approximate expression derived from peak‐normalized cross‐correlation values, and then quantitatively assesses how interplane bulk motion noise reduce the sensitivity of cross‐sectional angiograms. Finally, we developed a repetitive bulk motion correction method based on the estimated displacements and redundant volume scans. The correction does not require registration and angiogram reconstruction of low flow sensitivity frames, and the results of in vivo mice skin OCTA imaging experiments show that the proposed method can effectively reduce bulk motion noise caused by cardiac and respiratory motion and occasional shaking, and improve OCTA image quality, which has practical significance for clinical OCTA diagnosis and analysis. Abstract : Conventional registration methods focus on in‐plane displacement, while the bulk motion component perpendicular to B‐scans also introduces noise. We measured the displacement ( dy ) of this component using a specific scan protocol and an approximate expression. The flow sensitivity relative to dy was determined and used to reduce repetitive bulk motion noise caused by cardiac and respiratory motion, and the results show the improvement of optical coherence tomography angiography image quality.